Morphogenetic characteristics and demographic patterns of tillers on andropogon grass under different forage allowances - Araújo, Daniel Louçana da Costa; Oliveira, Maria Elizabete de; Lopes, João Batista; Alves, Arnaud de Azêvedo; Rodrigues, Marcônio Martins; Moura, Raniel Lustosa de; Santos, Maurílio Souza dos (Semina: Ciências Agrárias, 2015)
The objective of this study was to evaluate the morphogenetic and structural characteristics and the demographic patterns of tillering in the grass Andropogon gayanus Kunth var. Bisquamulatus (Hochst) Hack. cv. Planaltina subjected to three forage allowances: 11, 15 and 19% of the LW, under continuous grazing by goats. The experimental design for the evaluation of the pasture morphogenetic characteristics was set in (two) random blocks, with six replications (tussocks) within the block. To evaluate the tillering dynamics and population density, we adopted the experimental design of (two) random blocks, in a split-plot arrangement. In the plots, we evaluated the effect of forage allowances and in the subplots, the months of April, May and June. Forage allowances did not affect the leaf elongation rate, leaf senescence or the number of live leaves. The leaf appearance rate was highest at the masses of 11 and 15% of the LW. Managing the pasture with a forage allowance of 19% of the LW increases the stem elongation rate, leaf lifespan and the lengths of leaf and stem. The number of vegetative tillers and the tiller appearance and survival rates are not affected by the forage allowances from 11 to 19% of the LW.